Pulmonary Endarterectomy: Risk Factors for Early and Late Mortality - Yildizeli, Sehnaz Olgun; Arıkan, Hüseyin; Güngör, Sinem; Tufan, Aslı; Kocakaya, Derya; Ataş, Halil; Mutlu, Bülent; Tas, Serpil; Ak, Koray; Bekiroğlu, G. Nural; Yildizeli, Bedrettin (The Thoracic and Cardiovascular Surgeon, 2025)
Background Pulmonary endarterectomy (PEA) is a potentially curative treatment option for chronic thromboembolic pulmonary hypertension (CTEPH). This study aimed to identify predictors of short- and long-term outcomes after PEA for CTEPH patients, including age.Methods Patients who underwent surgery between March 2014 and January 2024 were included in the study. Perioperative and follow-up data were retrospectively studied, including age, in-hospital mortality, 1- and 5-year survival, and the length of intensive care unit (ICU) and hospital stays after PEA.Results In total, 834 consecutive patients (mean age 51 ± 15.3 years) underwent PEA and were included in the analysis. The in-hospital mortality rate was 7.8% (n = 65), while overall mortality rates at 1 and 5 years were 10.6% and 11.3%, respectively. The in-hospital mortality rate was 6.7% for patients <70 years compared with 12.4% for patients ≥70 years (p = 0.029). In the multivariate analysis of mortality, age (p = 0.007), and length of ICU stay (p = 0.028) emerged as independent predictors of in-hospital mortality, while the Charlson Comorbidity Index (p < 0.001) and 6-minute walk distance (p = 0.005) were also significant predictors of 1-year survival.Conclusion Despite higher short-term mortality rates, PEA was feasible and well-tolerated among elderly patients. Despite surgical advancements, careful patient selection remains crucial, particularly in the presence of comorbidities. Significant clinical and hemodynamic improvements were observed, along with favorable long-term survival outcomes.
Keywords: geriatrics; pulmonary embolism; pulmonary vascular resistance/hypertension